A study on the understanding of copyright law among the degree students in the Information Management Programme - a case of UiTM Kedah / Rozita Ahmad - Ahmad, Rozita (Faculty of Information Management, 2011)
The study attempts to investigate the level understanding of copyright law among the degree students in the Information Management Programme at UiTM Merbok. The aim of this study is to ensure that students should understand a copyright law to produce quality graduates. The objectives of this study are to identify the level of understanding of copyright law among students, to investigate the importance of copyright law, and to study the relationship between plagiarism and copyright law. The significance of this study are to upgrade and improve the level of understanding a copyright law among students, improve the awareness about plagiarism among student, and fulfil the Library & Information Management requirement. In this study, the populations consisted of the students at UiTM Merbok comprised 6839 students. The sample identified included the respondents who were from the Faculty Information Management, which consisted of 222 students. According Uma (2003), based on the total number students the Faculty of Information Management, the questionnaire that should be distributed was 140. To complete on this study, simple random technique was used. The questionnaire was divided into A, B, C, D, and E. The Social Science (SPSS) version 18.0 was use to analyse the data. Then, analysis was presented in charts and tables.